‘Green Box’ and Innovative Development of Agriculture in the Altai Territory of Russia - RUDOY, Evgeniy V.; SHELKOVNIKOV, Sergey A.; MATVEEV, Danil M.; SYCHEVA, Irina N.; GLOTKO, Andrey V. (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The paper reveals the changes occurred in the system of regulation and support of agriculture due to participation of Russia in WTO at the national and regional (example of the Altai territory) levels. The publication is aimed at estimation of potential impact caused by applying of basic commitments admitted by Russia in the area of agriculture in frames of WTO on innovative activity of agricultural economy. The authors applied such methods of research as abstract logical method, dialectic method, method of positive and normative analysis, and economico-statistical one etc. They analyze international experience of applying supporting instruments in agriculture and explain the necessity to refocus the state support on the ‘green box’ supports which is not limited by the requirements of WTO. The article makes conclusion that ‘green box’ exactly is able to build institutional environment contributing to strengthening innovative processes in the regional agriculture.